Morphological characterization of shallot (Allium cepa L. var. aggregatum) segregating populations obtained from natural-outcrossing in Ethiopial-outcrossing in Ethiopia - Tabor, G.; Mengistu, F. G.; Atinafu, G. (International Journal of Horticultural Science, 2024)
Shallot is a vegetable and condiment crop widely used in Ethiopia and globally. However, absence of improved and adaptable varieties has been the major cause of low productivity. Narrow genetic base of local shallot germplasm owing to vegetative reproduction of the crop, among others, has been the root cause of low productivity. Nevertheless, some plants within the germplasm were observed bolting and producing viable seeds, presenting an opportunity for genetic diversification. Consequently, a germplasm enhancement program was initiated using these naturally outcrossing genotypes where about eighty-one genotypes were generated. The present study was thus undertaken with the objective of characterizing, classifying, and selecting the eighty-one genotypes for future breeding activities. The genotypes were planted in 9x9 simple lattice design with two replications at Debre Zeit Agricultural Research Center (Ethiopia) during the dry (irrigated) season of 2021. The genotypes were evaluated for fifteen growth, yield, and quality traits. Significant variations were observed among the genotypes in terms of bulb yield, bulb height and diameter, total soluble solids, bolting percentage, and bulb skin color. Bulb yield of the genotypes ranged from 31.33 t/ha in DZSHT-79-1A to 9.63 t//ha in DZSHT-45-1A-1. DZSHT-51-2 (207.93 g) was the highest yielder per plant whereas DZSHT-065-6/90 (74.51 g) was the lowest yielder. DZSHT-14-2-1/90 had the thickest bulb (44.69 mm) significantly thicker than twenty two genotypes which had bulb diameter ranging from 28.92 mm to 20.29 mm. DZSHT-81-1/90 was a genotype with the longest bulb height (52.33 mm) while DZSHT-147-1C was a genotype with the shortest bulb (33.12 mm). DZSHT-307-1/90 had the highest TSS (16.78°Brix) significantly differing from DZSHT-002/07 which had the lowest TSS (11.17 °Brix). Dry matter of the genotypes ranged from 12.00% to 22.79%. DZSHT-004/07, DZSHT-111-2-1, DZSHT-41-2B and DZSHT-72-2 had DM% greater than 20% which coupled with greater than 14 °Brix could make them suitable for dehydrated shallots. Among the 81 genotypes characterized 4 (4.9%), 7 (8.6%), 13 (16.1%), 28 (34.6%) and 29 (35.8%) were yellow, golden, light red, red and dark red in colour, respectively. Fifteen of the genotypes had at least 50% bolting plants whereas twenty nine of the genotypes had less than 25% bolting. The results revealed that seven principal components explained approximately 76% of the observed variation. Cluster analysis grouped the genotypes into seven clusters, with the majority falling into three clusters. The study successfully identified genotypes with diverse and important traits and availed both the genotypes and the information for future breeding programs. These genotypes could be used for the development of improved hybrid and open pollinated shallot varieties with higher yield, quality and pest resistance/tolerance attributes.